Substitusi Tepung Daun Katuk (Sauropus Androgynus (L) Merr) Terhadap Elongasi Dan Daya Terima Mie Basah - Hasanah Itsnaini, Nur, Rusdin Rauf, S.TP., M.P, Fitriana Mustikaningrum, S.Gz., M.Sc (2015)
Backround : National development programs by the goverment of Indonesia is currently one of which ensure increased food production and more diverse consumption. Diversification of food in this case is a vegetable (katuk leaves) can be used as an additional ingredient products such as noodle. Purpose : The purpose of this study was to determine the effect of the use of katuk leaves as a substituent of wheat flour to elongation and acceptance of wet noodle. Method : This research method is experimental research with a completely randomized design that use four additional variations (0%, 10%, 20%, and 30%). Statistical analysis to elongation and acceptability use One Way Anova test and is an impact, will test again by a Duncan Multiple Range Test (DMRT). Result : Elongation in the wet noodle has a value of p<0,05 (0,003) is no substitution effect to elongation katuk leaves of wet noodle. While the acceptability of the color, savor, flavor, texture, and overall liking by panelist indicate that the much preferred is wet noodle with substitution of 0% katuk leaves flour of total flour. Coclution : There is a substitution effect katuk leaves flour in the production of wet noodle to elongation and acceptance wet noodle. Suggestion : Based on highest panelist acceptance, the suggest is substitute flour of katuk leaves at least when compared with controls. Continue research is needed on how to remove do not like on katuk leaves savor. Keywords : katuk leaves flour, elongation, acceptability, wet noodle Kepustakaan : 33 (1981-2013)